EFEKTIVITAS PENERAPAN E-COURT PENGADILAN NEGERI SORONG KELAS I B DALAM PERKARA PERDATA PERMOHONAN PENGANGKATAN WALI BAGI ANAK - Diniawantari, Citra Diniawantari; Latif, Udin (Muadalah : Jurnal Hukum, 2023)
The judiciary in Indonesia adheres to the principle of Containe Justice or the principle of simple, fast and low-cost justice. However, in reality, the judiciary in Indonesia is overburdened, slow and expensive, so the Supreme Court has reformed it by launching an electronic court system (e-Court) service as regulated in Perma Number 3 of 2018 concerning Electronic Court Administration, which was later abolished and refined in accordance with Perma Number 1 of 2019 concerning Electronic Administration of Cases and Trials in Court. Then it was refined again with Perma Number 7 of 2022 concerning Amendments to PERMA Number 1 of 2019 concerning Electronic Administration and Trials in Court. Based on this, this research aims to find out how effective e-Court is in resolving civil cases regarding applications for the appointment of guardians for children and for find out the obstacles experienced by the Sorong Class I B District Court in implementing e-Court.